2020
DOI: 10.3892/mmr.2020.11601
|View full text |Cite
|
Sign up to set email alerts
|

Potential role of lncRNA HULC/miR‑128‑3p/RAC1 axis in the inflammatory response during LPS‑induced sepsis in HMEC‑1 cells

Abstract: Sepsis is a serious clinical condition characterized by systemic inflammation. The long noncoding rna (lncrna) highly upregulated in liver cancer (Hulc) was validated to partake in the development of sepsis. The present study aimed to investigate the potential mechanism of Hulc in lipopolysaccharide (lPS)-induced sepsis. reverse transcription-quantitative polymerase chain reaction (rT-qPcr) and western blot analysis was employed to examine the expression of Hulc, microrna (mir)-128-3p, rac family small GTPase … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
4
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 36 publications
2
4
0
Order By: Relevance
“…In the present study, the effect of LPS on HBEpCs was measured. The data from RT-qPCR, MTT assay, cell apoptosis assay, and Western blot suggested that LPS treatment reinforced apoptosis and inflammatory responses and inhibited viability of HBEpCs, which was in line with previous studies [ 22 ], thus indicating the successful establishment of a sepsis model in vitro .…”
Section: Discussionsupporting
confidence: 89%
“…In the present study, the effect of LPS on HBEpCs was measured. The data from RT-qPCR, MTT assay, cell apoptosis assay, and Western blot suggested that LPS treatment reinforced apoptosis and inflammatory responses and inhibited viability of HBEpCs, which was in line with previous studies [ 22 ], thus indicating the successful establishment of a sepsis model in vitro .…”
Section: Discussionsupporting
confidence: 89%
“…HULC and urothelial carcinoma-associated 1 increased the expression of IL6, vascular cell adhesion molecule 1, and intracellular adhesion molecule 1 after LPS-induced inflammation in an endothelial cell model, thereby impairing vascular endothelial functions ( 126 ). In consistent with the previous study, HULC silencing could reverse the sepsis process stimulated by LPS by modulating miR-128-3p/Rac family small GTPase 1 axis in human umbilical vein endothelial cells (HUVECs) ( 69 ). Additionally, MALAT1 was significantly elevated in LPS-stimulated CMVECs, accompanied by the increase of permeability and apoptosis of CMVECs ( 46 ).…”
Section: Lncrnas In Sepsis-induced Endothelial Cell Dysfunctionsupporting
confidence: 91%
“…Many of the miRNAs altered between 14 and 30 days have been found in previous studies to have roles related to mammary gland development. For instance, miR-128-3p was upregulated in the second week postpartum and is known to target RAC1 (Rac family small GTPase 1), the key GTPase in clearance of apoptotic cells during involution in mammary gland remodeling 69 , 70 . miR-27a-5p was downregulated in milk EVs.…”
Section: Discussionmentioning
confidence: 99%